Measuring Exocytosis Rate Using Corrected Fluorescence Recovery After Photoconversion. (31st March 2016) - Luo, Nan; Yan, An; Yang, Zhenbiao
Abstract : An optical method is developed to measure the exocytosis rate of plasma membrane or extracellular matrix proteins. In this method, the protein‐of‐interest is tagged with a green‐to‐red photoconvertible fluorescent protein; after photoconverting a region‐of‐interest on the cell surface, exocytosis‐dependent and ‐independent trafficking events are tracked simultaneously for accurate determination of exocytosis rate. Abstract : Exocytosis plays crucial roles in regulating the distribution and function of plasma membrane (PM) and extracellular matrix proteins. However, measuring the exocytosis rate of a specific protein by conventional methods is very difficult because of exocytosis‐independent trafficking such as endocytosis, which also affects membrane protein distribution. Here, we describe a novel method, corrected fluorescence recovery after photoconversion, in which exocytosis‐dependent and ‐independent trafficking events are measured simultaneously to accurately determine exocytosis rate. In this method, the protein‐of‐interest is tagged with Dendra2, a green‐to‐red photoconvertible fluorescent protein. Following the photoconversion of PM‐localized Dendra2, both the recovery of the green signal and the changes in the photoconverted red signal are measured, and the rate of exocytosis is calculated from the changing rates of these two signals.